PENGGUNAAN MEDIA POWER POINT INTERAKTIF DALAM PEMBELAJARAN DI SEKOLAH SUATU KENISCAYAAN DI ERA DIGITAL - Ridhwan M. Daud (FITRAH: International Islamic Education Journal, 2023)
The industrial revolution from 4.0 to 5.0 has recently made it easier for humans to complete their tasks optimally in all fields. With the help of this high industry everything can be done automatically. This can also be done in the learning process at school. In the learning process at school, this latest computerized industrial revolution has made it easy for a teacher to use interactive power point learning media in presenting his learning material. This interactive power point media in theory if it can be designed and used properly will be able to increase student motivation, interest and learning outcomes. This is because this computer-based media can present concise learning material in the form of slides that are attractive and easy to understand. Many studies on this subject have been carried out in schools, all of which yield positive values, namely that they can significantly increase student motivation, interest, enjoyment and learning outcomes. Therefore it is highly recommended for all teachers to learn to create interactive power point learning media and use them in learning in this digital era.